Massive inborn angiogenesis in the brain scarcely raises cerebral blood flow - Vogel, Johannes; Gehrig, Mathias; Kuschinsky, Wolfgang; Marti, Hugo (Journal of cerebral blood flow & metabolism, 2004)
The functional consequences of increased capillary densities in the brain resulting from vascular endothelial growth factor (VEGF165) overexpression are unknown. Therefore, the authors measured local CBF using the iodo-[14C]antipyrine technique in transgenic mice expressing brain-specifically sixfold higher VEGF165 levels and in nontransgenic littermates. To reveal possible compensatory vasoconstriction, CBF was also measured during severe hypercapnia (PaCO2 > 130 mm Hg). Simultaneously, local capillary density, perfusion state, and blood-brain-barrier permeability were assessed. Using the 2-[14C]deoxyglucose method, metabolic effects of VEGF overexpression could be excluded. In transgenic mice all capillaries showed normal morphology and a tight blood-brain barrier. However, 3% nonperfused capillaries in some brain structures indicate ongoing angiogenesis. Capillary density was drastically increased in transgenic mice in white matter structures (70% to 185%), the dentate gyrus (143%), and caudate nucleus (86%). In all other brain structures investigated, capillary densities were moderately increased by approximately 20%. Normocapnic CBF did not differ between transgenic and nontransgenic mice. During maximal hypercapnic vasodilation, CBF was 20% to 30% higher in transgenic mice, although only in brain structures where capillary density was increased more than twofold. These findings suggest that attenuated CBF in transgenic mice during normocapnia is only partly due to a compensatory vasoconstriction, and that microvascular networks in transgenic brains might be ineffectively constructed.